A realização do fonema lateral /l/ em coda silábica em variedades do português brasileiro e do inglês - Lacerda, Willian Ferreira Furtado de (2021)
This study addresses linguistic variation at the phonetic-phonological level, seeking to identify points of convergence in the results of research that investigated the realization of the lateral phoneme /l/ in syllabic coda position, both in Brazilian Portuguese (BP) and in English, addressing both languages in the context of mother tongue (MT) and foreign language (L2). Although there are other variants, we predominantly find, in syllabic coda, the lateral in the velarized and vocalized forms. We draw on authors such as Tarallo (1990), Labov (2008 [1972]) and others to deal with Variationist Sociolinguistics; Giles, Coupland e Coupland (1991) and Giles et al (2011) to address the Accommodation Theory; Oppenheim (1992), Cardoso (2015) and others on linguistic attitudes; Wilkins (1994) and Oliveira (2014) on teaching English as L2. Methodologically, we analyzed eleven studies that investigated the phenomenon in question. The results indicated that both linguistic and social factors act in the speaker's decision (conscious or not) to choose one variant or another while they speech: the preceding phonological context was relevant in 10 of the 11 studies analyzed; the variables location, tone and exposure time, although they were not controlled by all the researches, proved to be relevant in all those that controlled them; on the other hand, the variables gender, age group, position of the coda in the word, following phonological context, level of education and extension of the word were also important, as they were considered relevant in most of the studies that controlled them. These results reaffirm the inseparability of the pair language and society, considering that the variables relevant to the phenomenon are both linguistic and social, and reaffirm the importance of studies in the field of Sociolinguistics and its ramifications.